Microbial Adhesion on Circular Obstacles: An Optimization Study - Faúndez, Tamara; Espinoza, Bastián; Soto, Rodrigo; Guzmán-Lastra, Francisca (Frontiers in Physics, 2022)
Microbial filtration is an important process with applications in environmental, mining, and sanitary engineering. Here, we study the interplay between the motility of microswimmers and the imposed flow, to determine the adhesion of bacteria at the surface of the solid obstacle. For that, we perform numerical simulations of active Brownian particles interacting with a single cylindrical obstacle when an imposed laminar flow is present. Highly and weakly persistent swimmers are studied, representing extreme cases of bacteria used in experiments and we vary the swimmers' velocity u_0, the imposed flow velocity U_∞, and the obstacle radius R. Starting with no swimmers close to the cylinder, we inject them steadily until a constant number of swimmers is adhered to the obstacle surface. The deposition/erosion process is characterized by the number of bacteria in contact with the obstacle, quantified by the average coverage of the cylinder surface λ_trap, and the relaxation time to reach the steady state τ_trap. Two regimes are found. The Brownian deposition is attained when swimmer velocities are smaller than the imposed flow. In this case, particles can diffuse across the streamlines and settle around the obstacle covering the whole perimeter, forming multiple layers. The direct interception is obtained when the particle's velocities are larger, reaching the obstacle by direct swimming, in which case they form approximately one layer on the obstacle surface. It is found that λ_trap decreases with u_0 and R, but the dependence with the imposed flow U_∞ is non-monotonic, with and optimum coverage for intermediate flows, given by the crossover of the two regimes. The relaxation rate τ_trap decreases with u_0 and increases with R. The dependence of τ_trap with U_∞ is more complex, depending on the persistence of the swimmers. The existence of an optimum value of the flow velocity to reach maximum values of the number of deposited swimmers, is an important design information for different applications that use microbial filtration. Finally, in general, it is found that optimal adhesion, that is larger values of λ_trap and smaller values of τ_trap, are obtained for more-persistent swimmers moving at small velocities, interacting with small obstacles.